The Failure of Governance and Internal Controls in Preventing Fraud in the Company - Muslim, Muslim (Advances in Managerial Auditing Research, 2025)
Purpose: This study investigates the organizational and individual factors that contribute to the failure of corporate governance and internal controls in preventing fraud. It highlights the role of senior management, board oversight, and conflicts of interest in enabling fraudulent activities within organizations. Research Design and Methodology: The research utilizes a systematic literature review (SLR) approach to analyze existing studies on corporate governance, internal controls, and fraud prevention. The study synthesizes findings from various disciplines, including governance theories, forensic accounting, and organizational behavior, to identify patterns and trends contributing to governance failures. Findings and Discussion: The findings reveal that governance failures often arise from weak board oversight, a lack of commitment from senior management, and conflicts of interest within audit committees. Additionally, an overemphasis on regulatory compliance at the expense of ethical standards and short-term financial pressures exacerbates the risk of fraud. The study discusses how these structural and behavioral weaknesses create opportunities for fraud and how technologies like AI and blockchain, combined with ethical corporate culture, can strengthen internal controls and fraud detection systems. Implications: The research emphasizes the need for companies to foster ethical values alongside technological advancements in internal controls. It provides practical recommendations for improving governance systems through substantial leadership commitment, independent board oversight, and integration of advanced technology to detect and prevent fraud.